2013
DOI: 10.1134/s1070427213090114
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a chelating sorbent based on pyridylethylated polyethylenimine for recovering transition metal ions

Abstract: Abstract-A method was developed for preparing a chelating amino polymer, pyridylethylpolyethylenimine with maximal degree of substitution, by polymer-analogous transformations of branched polyethylenimine in reaction with 2-vinylpyridine. The ability of cross-linked pyridylethylpolyethylenimine with the degree of substitution of 0.32 to sorb Cu 2+ , Ni 2+ , Co 2+ , Zn 2+ , Cd 2+ , Mn 2+ , and Pb 2+ ions present simultaneously in solution was evaluated. In an ammonium acetate sorption system (pH 3.5-4.0), the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Although the calculated affinity constants are apparent, the difference between the values of K AF of PEI-BD and for Cu­(II), Ni­(II), Co­(II) ions correlates with the stability of corresponding metal ion complexes with N-ligands, which is usually 3–6 orders of magnitude higher for Cu­(II) than for Ni­(II) complexes . It was earlier reported that much higher stability of Cu­(II) complexes allowed selective separation of Cu­(II) ions from a mixture with Ni­(II), Co­(II), Zn­(II), Cs­(I), Mn­(II), and Pb­(II) ions using a polyethylene-based sorbent in batch at pH 3.5–4.0 . However, thermodynamic stability does not say anything about the sorption rate constants and cannot predict the efficacy of ion separation under dynamic conditions: in other words, highly affine sorption centers are not necessarily the fastest and vice versa.…”
Section: Resultsmentioning
confidence: 93%
“…Although the calculated affinity constants are apparent, the difference between the values of K AF of PEI-BD and for Cu­(II), Ni­(II), Co­(II) ions correlates with the stability of corresponding metal ion complexes with N-ligands, which is usually 3–6 orders of magnitude higher for Cu­(II) than for Ni­(II) complexes . It was earlier reported that much higher stability of Cu­(II) complexes allowed selective separation of Cu­(II) ions from a mixture with Ni­(II), Co­(II), Zn­(II), Cs­(I), Mn­(II), and Pb­(II) ions using a polyethylene-based sorbent in batch at pH 3.5–4.0 . However, thermodynamic stability does not say anything about the sorption rate constants and cannot predict the efficacy of ion separation under dynamic conditions: in other words, highly affine sorption centers are not necessarily the fastest and vice versa.…”
Section: Resultsmentioning
confidence: 93%
“…PEI-based materials have been intensively investigated as efficient sorbents for many heavy metal ions, , which, however, showed in most cases strong preference for Cu­(II) ions in terms of affinity. The preferential adsorption of Cu­(II) over Zn­(II) and Cd­(II) ions was earlier shown in batch experiments for a PEI-based magnetic porous sorbent . The much higher stability of Cu­(II) complexes allowed selective separation of Cu­(II) ions from a mixture with Ni­(II), Co­(II), Zn­(II), Cs­(I), Mn­(II), and Pb­(II) ions using a polyethylene-based sorbent in batch at pH 3.5–4.0 . However, in fixed-bed applications, the sorption difference in kinetics can affect the overall performance of the sorption columns since high affinity sites can be not the fastest ones.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Cryogels are now considered as promising materials for removal of metal ions, organic pollutants, and small molecules from biological media, taking advantage of the good transport properties provided by supermacroporous matrices. We have focused here on Cu­(II), Zn­(II), and Cd­(II) ion sorption for two main reasons: (i) these metal ions are very common pollutants in natural and waste waters, and (ii) their sorption on PEI-based sorbents from single and multicomponent solutions have been reported in the literature that allows comparison of RCD model results with other experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4]13 However, better commercial availability of synthetic polymers and more developed methods of their functionalization are often used as the main arguments in the discussion on the advantages and shortcomings of the application of biopolymers. The dependence of selectivity and sorption capacity not only on the type of the introduced functional fragments but also on the structure of the polymer backbone 14 and the type of the cross-linking agent 15 was revealed for some pyridyl and bipyridyl derivatives, which had been known as efficient chelating sorbents for precious metals. 1,6,13,14,16,17 We have recently demonstrated that pyridylethylated derivatives of polyallylamine (PAA), polyethylenimine (PEI), and chitosan with the same degree of substitution significantly differ in their efficiency of binding transition-metal ions, which was correlated with the difference in the structure and stability of the complexes formed.…”
Section: Introductionmentioning
confidence: 99%
“…The dependence of selectivity and sorption capacity not only on the type of the introduced functional fragments but also on the structure of the polymer backbone 14 and the type of the cross-linking agent 15 was revealed for some pyridyl and bipyridyl derivatives, which had been known as efficient chelating sorbents for precious metals. 1,6,13,14,16,17 We have recently demonstrated that pyridylethylated derivatives of polyallylamine (PAA), polyethylenimine (PEI), and chitosan with the same degree of substitution significantly differ in their efficiency of binding transition-metal ions, which was correlated with the difference in the structure and stability of the complexes formed. 18 However, due to the lack of systematic Here we report on the effect of the backbone structure on the sorption properties of pyridylethyl-containing derivatives of polyallylamine, polyethylenimine, and chitosan toward Au(III), Pt(IV), and Pd(II) ions and show how pyridylethylation affects the speciation of noble-metal ions in the sorbent phase and the efficiency of their elution with HCl and HCl/thiourea solutions.…”
Section: Introductionmentioning
confidence: 99%